A SURVEY OF THE AVAILABILITY OF LAMDONG PROVINCIAL ONLINE SERVICE APPLICATIONS - Hồ Quang Thanh (Tạp chí Khoa học Đại học Đà Lạt)
This research is modeled on the Technology Acceptance Model (TAM) to develop and validate the components and factors that affect the acceptance and availability of online public service transactions in the community of enterprises in Lamdong province. Cronbach's Alpha reliability analysis, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) are used to test the scales and relationships in a theoretical model for Public Service Systems Online (PSSO). Data collected from 287 enterprises in Lamdong province were tested in the research. The results show that: Support agencies; The usefulness; and The ease of use affect attitude toward using and the intention of using online trading. The research model accounts for about 75% of the variation in acceptance and availability of online public services.